Medievalism and discrimination - Fugelso, Karl (D.S. Brewer, 2019)
The difficult and nuanced issue of discrimination - race, gender, ethicity, religion - is the focus of this volume.
A Transcription of Helen Waddell's Notes on the Roman de la Rose and Christine de Pizan: Manuscript Queen's University Belfast 18/1/cContributors
Keywords: Medievalism.; Discrimination -- History -- To 1500.; Médiévisme.; Discrimination -- Histoire -- Jusqu'à 1500.; Medievalism (cultural movement); Discrimination; Medievalism; To 1500; History